Exploring SME Advice and Training Needs for Entrepreneurial Rural Firms. (May 2013) - Martin, Lynn M.; Warren-Smith, Izzy; Schofield, Clare; Millman, Cindy
This paper reports on two studies carried out to investigate business support needs in the rural south-east and south-west of the UK West Midlands region. The researchers surveyed a sample of 494 micro, small and medium-sized enterprises to provide support for better decision making by regional providers of training and advice in identifying the needs of these firms. The overall findings suggest that rural areas need to be seen within their own contexts and that support requires differentiation to meet specific needs, particularly where there is evidence of curtailed innovation. More detailed research into innovation across rural areas might identify reasons for emerging trends and explain why some rural areas are more entrepreneurial than others. The study findings revealed that innovation was evident in one-third of the businesses, with growth likely to be given the right support, although there was evidence of greater levels of entrepreneurial behaviour in the area with more immigrants and a better transport infrastructure.